(untitled) (Bangladesh Journal of Zoology, 2015)
Efficacy of methanolic extracts of different indigenous plant parts, such as the leaves and barks of neem (Azadirachta indica); leaves of basil (Ocimum basilicum), mahua (Madhuca indica), lantana (Lantana camara), eucalyptus (Eucalyptus globulus), surjokonna (Spilanthes acmella) and flowers of golden shower (Cassia fistula), rosy periwinkle (Catharanthus roseus) and orchid (Mokara charkuan) were tested against the oviposition behavior of the melon fly, Bactrocera cucurbitae (Coquillett) (Diptera : Tephritidae). Most effective botanicals as attractants were observed in C. fistula and M. indica. In choice test, the percentage of B. cucurbitae pupae emerged were 0.0 in the leaves and barks of A. indica, 0.22 in flowers of M. charkuan, 1.43 in leaves of O. basilicum, 2.68 in leaves of L. camara, 6.83 in flowers of C. roseus, 5.51 in leaves of S. acmella, 13.27 in leaves of E. globules, 19.99 in flowers of C. fistula and 14.09 in leaves of M. indica. In nochoice test, the respective percentages of B. cucurbitae pupae emerged were 0.0, 2.19, 2.29, 11.68, 10.65, 12.34, 7.73, 6.76, 13.66 and 15.16 for the leaves of A. indica, bark of A. indica, in flowers of M. charkuan, in leaves of O. basilicum, in flowers of L. camara, in flowers of C. roseus, in leaves of S. acmella, in leaves of E. globules, in flowers of C. fistula and in leaves of M. indica. Phytochemical screening of the methanolic crude extracts of the botanicals showed that M. indica was strongly positive for steroid; C. fistula were strongly positive for alkaloid, flavonoids and glycoside and M. charkuan was weakly positive for carbohydrates, alkaloid and steroid. Bangladesh J. Zool. 41(1): 105-112, 2013